2017
DOI: 10.1177/2325967117724431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome Reporting in Youth ACL Literature Is Widely Variable

Abstract: Background:Advances in anterior cruciate ligament (ACL) reconstruction procedures in pediatric and adolescent patients have resulted in an increase in recent clinical studies on this topic. However, the consistency with which outcome measures are reported in this demographic is unknown.Purpose:To document outcome reporting patterns of youth ACL reconstruction studies in high-impact journals.Study Design:Systematic review; Level of evidence, 4.Methods:All articles published in 5 high-impact orthopaedic journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 47 publications
1
31
0
2
Order By: Relevance
“…53 Furthermore, a 2017 review on reporting trends in youth ACL reconstructions found diverse definitions of skeletal maturity, inconsistently reported objective outcome measures, and the use of patient-reported outcome measures (PROMs) that were developed and validated for adults. 10 Inconsistent and nonstandardized outcome reporting reduces the possibility of comparing and interpreting results across different studies. It is unknown if the high variability in outcome measures seen in adults and adolescents is present in the literature on pediatric ACL injuries.…”
mentioning
confidence: 99%
“…53 Furthermore, a 2017 review on reporting trends in youth ACL reconstructions found diverse definitions of skeletal maturity, inconsistently reported objective outcome measures, and the use of patient-reported outcome measures (PROMs) that were developed and validated for adults. 10 Inconsistent and nonstandardized outcome reporting reduces the possibility of comparing and interpreting results across different studies. It is unknown if the high variability in outcome measures seen in adults and adolescents is present in the literature on pediatric ACL injuries.…”
mentioning
confidence: 99%
“…The lack of high-quality evidence in studies identified in the present systematic review is consistent with prior investigations into the literature concerning pediatric and adult ACL reconstruction. 13 , 114 The vast majority of studies were conducted retrospectively, which constrains the data available for analysis and precludes use of newer PROMs, which have greater applicability to pediatric populations. It is important to consider that many studies were conducted prior to the development of survey instruments validated in pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study evaluating the pediatric ACL literature from 2010 to 2016 in a limited number of journals demonstrated significant heterogeneity in clinical outcomes reporting, consistent with the findings of the current review. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we need to understand how to apply the pediatric PROMIS domains to our pediatric and adolescent patients, especially in sports medicine that has very few age-appropriate PROMs despite experiencing a large increase in the incidence of youth sports injuries and treatment methods. [17][18][19][20][21][22] Finally, we need to work with our institutions and specialty societies to guide the conversation around how these data will be used by the government and thirdparty payers. As PROMs such as PROMIS become linked to reimbursement, we as a profession want a seat at the table as these policies are being created.…”
Section: See Related Article On Page 1113mentioning
confidence: 99%